2001
DOI: 10.1054/bjoc.2001.2056
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for NQO1 (NAD(P)H:quinone oxidoreductase, EC 1.6.99.2) mediated therapy of bladder cancer based on the pharmacological properties of EO9

Abstract: The indolequinone EO9 demonstrated good preclinical activity but failed to show clinical efficacy against a range of tumours following intravenous drug administration. A significant factor in EO9's failure in the clinic has been attributed to its rapid pharmacokinetic elimination resulting in poor drug delivery to tumours. Intravesical administration of EO9 would circumvent the problem of drug delivery to tumours and the principal objective of this study is to determine whether or not bladder tumours have elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…The results of the immunohistochemical studies clearly demonstrate that a broad spectrum of NQO1 expression exists with a significant number of patients' tumours containing high NQO1 levels (Table I). These results are entirely consistent with previous studies 24,25 and suggest that NQO1 is a good target for drug development in bladder cancer. A narrow range of P450R protein levels were observed with most tumours having moderate to high protein expression, a result which is again consistent with previous findings in bladder, lung and breast cancers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the immunohistochemical studies clearly demonstrate that a broad spectrum of NQO1 expression exists with a significant number of patients' tumours containing high NQO1 levels (Table I). These results are entirely consistent with previous studies 24,25 and suggest that NQO1 is a good target for drug development in bladder cancer. A narrow range of P450R protein levels were observed with most tumours having moderate to high protein expression, a result which is again consistent with previous findings in bladder, lung and breast cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst a detailed discussion of the relative merits of immunohistochemistry and semiquantitative RT-PCR is beyond the scope of this article, issues such as the relationship between gene expression (or immunoreactive protein) and enzyme activity, spatial localisation of mRNA or protein in tumour as opposed to stromal cells and the semiquantitative nature of both assays are frequently raised points that affect both methodologies used to a greater or lesser extent. The antibodies used in our study have previously been shown to selectively stain for both NQO1 23,24 and P450R (data not shown) with good correlations between immunoblotting, protein staining and enzyme activity in cell cultures and tumours. The presence of intratumour heterogeneity with regard to NQO1 protein expression (Figs.…”
Section: Discussionsupporting
confidence: 54%
“…We also identified N33, a tumor suppression gene (Levy et al, 1999), and several apoptosis-related genes (e.g. caspase-4 and quinone-1, the latter was previously shown to be overexpressed in human bladder cancer; Choudry et al, 2001). Overall, of the 23 known genes identified as significantly upregulated in TCC, eight were previously related to bladder carcinoma.…”
Section: Potential Diagnostic Markers For Noninvasive Tccmentioning
confidence: 65%
“…Major risk factors for bladder cancer are cigarette smoking and occupational exposures to chemicals, such as aromatic amines and polycyclic aromatic hydrocarbons (17). A recent study found that NQO1 expression is elevated in bladder tumor tissues in a subset of patients (50% had a greater than four times increase in NQO1 level), suggesting that NQO1 plays a role in bladder carcinogenesis (18).…”
Section: Introductionmentioning
confidence: 99%